This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Great application of Stolz-Cesaro!
@Harsh Shrivastava It was your turn now. :)
Split it like this:
n → ∞ lim ( n ! ) 1 / n n + ( n ! ) 1 / n 1
Let y = n → ∞ lim ( n ! n n ) 1 / n + 0
Taking log both the sides lo g y = n → ∞ lim n 1 lo g ( n − 0 n . n − 1 n . n − 2 n . . . . . . n − ( n − 1 ) n )
lo g y = n → ∞ lim n 1 r = 0 ∑ n − 1 lo g ( 1 − n r 1 )
lo g y = 0 ∫ 1 lo g ( 1 − x 1 ) d x
lo g y = 1 y = e
We can use Stirling's approximation in the form
ln ( n ! ) = n ln ( n ) − n + O ( ln ( n ) ) .
With L being the given limit, we then have that
ln ( L ) = lim n → ∞ ( ln ( n + 1 ) − n 1 ∗ ln ( n ! ) ) =
lim n → ∞ ( ln ( n + 1 ) − ln ( n ) + 1 − n 1 ∗ O ( ln ( n ) ) ) =
1 + lim n → ∞ ( ln ( 1 + n 1 ) ) − lim n → ∞ ( n 1 ∗ O ( ln ( n ) ) ) = 1 + ln ( 1 ) − 0 = 1 .
(Note that, by L'Hopital's rule,
lim x → ∞ x ln ( x ) = lim x → ∞ 1 x 1 = 0 ,
the result then holding true for the analogous discrete limit.)
This implies that L itself is e 1 = e .
Stirling's approximation really is powerful.
Problem Loading...
Note Loading...
Set Loading...
We apply a variation of Stolz–Cesàro theorem:
Because ( n ! ) 1 / n n + 1 = n n ! ( n + 1 ) n , let x n = n ! ( n + 1 ) n , then n → ∞ lim x n − 1 x n = n → ∞ lim ( 1 + n 1 ) n = e , which is finite.
Thus Stolz–Cesàro theorem is applicable. With the limit equals to e .